Stretchable in-situ soaking double-network hydrogel electrolyte as well as preparation method and application thereof

By using stretchable in situ immersion of dual network hydrogel electrolytes in zinc ion batteries, the problems of low ion conductivity and reduced mechanical properties of hydrogel electrolytes in zinc ion batteries in the prior art are solved, and the problem of low ion conductivity and reduced mechanical properties in zinc ion batteries in the application of zinc ion batteries is realized. Higher electrochemical properties and cycle stability.

CN119431661AActive Publication Date: 2025-02-14SOUTHWEST PETROLEUM UNIV

Patent Information

Application Number
CN202411572104.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing hydrogel electrolytes have problems such as low ionic conductivity, reduced mechanical properties and reduced battery performance in zinc ion battery applications.

Method used

The preparation method of stretchable in situ soaking double network hydrogel electrolyte is adopted, by adjusting the pH of the precursor solution, using amide and acid anhydride monomer copolymer, and adding trace amounts of zinc ions on both sides of the hydrogel The solution was soaked in situ.

Benefits of technology

It improves the electrochemical performance of hydrogel electrolyte, reduces the consumption of zinc salt, enhances mechanical properties and ionic conductivity, inhibits the formation of dendrites, and shows good cycling stability in zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431661A_ABST
    Figure CN119431661A_ABST
Patent Text Reader

Abstract

The invention provides a stretchable in-situ soaking double-network hydrogel electrolyte as well as a preparation method and application thereof. The method comprises the following steps: preparing a uniformly mixed solution of a first monomer, a second monomer, an initiator, a cross-linking agent and an accelerator; adjusting the pH value of the mixed solution, and uniformly stirring to obtain a precursor solution; removing bubbles in the precursor solution, and carrying out free radical polymerization at a preset temperature to form hydrogel; and cutting the hydrogel, dropwise adding a trace amount of a salt solution containing zinc ions to two sides of the cut hydrogel, and clamping the hydrogel between two pole pieces for in-situ soaking to obtain the hydrogel electrolyte. By using the independent hydrogel electrolyte, side reaction on the surface of the zinc negative electrode, growth of dendritic crystals and electrode corrosion can be inhibited, and meanwhile, the electrochemical performance of the zinc ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aqueous zinc ion battery polymer electrolytes, and in particular to a stretchable in-situ immersion double network hydrogel electrolyte and a preparation method and application thereof. Background Art

[0002] In the pursuit of the net-zero emission vision, energy storage combined with carbon-free sustainable generators plays an unquestionable role. Rechargeable lithium batteries have been widely used in industry due to their high energy density and long cycle life. However, the scarcity of lithium reservoirs, safety issues of non-aqueous electrolytes and high costs restrict their future development. Aqueous zinc-ion batteries (ZIBs) have the advantages of large theoretical capacity, low redox potential, high safety, low cost and low toxicity, and their simple structure, high specific capacity and energy density make them the most promising alternative batteries.

[0003] Electrolytes are one of the key components that control the reaction mechanism and kinetics in ion batteries. They include liquid, quasi-solid and solid electrolytes. Liquid electrolytes usually have the highest ionic conductivity among the three electrolytes, but their fluidity places strict requirements on the battery packaging process, and the problems of leakage and evaporation still exist. Solid electrolytes alleviate the concerns of liquid electrolytes, but due to their low room temperature ionic conductivity and high interface resistance, the electrochemical performance is far from satisfactory. In addition, their brittleness limits large-scale production. Compared with liquid and solid electrolytes, quasi-solid electrolytes (i.e., hydrogel electrolytes) provide good ionic conductivity, interface properties and mechanical deformation ability, while having appropriate mechanical stiffness and elasticity, which can act as a diaphragm to prevent dendrite growth and reduce the risk of short circuit. However, in the existing research on hydrogel electrolytes used in zinc-ion batteries, high-strength hydrogels often have low ionic conductivity, which will reduce the mechanical properties after soaking in a large amount of zinc salt aqueous solution, and will cause the battery performance to decline. Summary of the invention

[0004] The purpose of the present invention is to solve at least one of the above-mentioned deficiencies in the prior art. For example, one of the purposes of the present invention is to provide a method for preparing a stretchable in-situ soaked double network hydrogel electrolyte; the second purpose of the present invention is to provide a stretchable in-situ soaked double network hydrogel electrolyte; the third purpose of the present invention is to provide an aqueous zinc ion battery; the fourth purpose of the present invention is to provide an application of a stretchable in-situ soaked double network hydrogel electrolyte in the preparation of a battery.

[0005] In order to achieve the above objectives, the first aspect of the present invention provides a method for preparing a stretchable in-situ immersion double network hydrogel electrolyte.

[0006] The method may include the following steps: preparing a uniform mixed solution of a first monomer, a second monomer, an initiator, a cross-linking agent and an accelerator; adjusting the pH of the mixed solution, stirring it uniformly, and obtaining a precursor solution; removing bubbles in the precursor solution, and performing free radical polymerization at a preset temperature to form a hydrogel; cutting the hydrogel, and dripping a small amount of a salt solution containing zinc ions on both sides of the cut hydrogel, and sandwiching it between two electrodes for in-situ immersion to obtain a hydrogel electrolyte.

[0007] Optionally, the first monomer is an amide monomer, the second monomer is an anhydride monomer, and the mass ratio of the first monomer to the second monomer is 1:(0.5-10).

[0008] The amide monomer may include one of acrylamide, methacrylamide, N-isopropylacrylamide, N,N-diethylacrylamide, isobutoxymethylacrylamide, diacetone acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 2-(trifluoromethylsulfonamido)ethyl-methacrylate and N-allyl-2,2,2-trifluoroacetamide and derivatives thereof.

[0009] The anhydride monomer may include one of maleic anhydride, succinic anhydride, bromomaleic anhydride, dimethyl maleate, diethyl maleate, dibutyl maleate, diisooctyl maleate, maleic acid, fumaric acid, dibutyl fumarate and bis(2-ethylhexyl) fumarate and derivatives thereof.

[0010] Optionally, the initiator accounts for 0.2-2% of the sum of the mass of the first monomer and the second monomer, and the initiator may include one of potassium persulfate, sodium persulfate, ammonium persulfate and azobisisobutyronitrile.

[0011] Optionally, the crosslinking agent accounts for 0.01-1% of the sum of the mass of the first monomer and the second monomer, and the crosslinking agent may include one or more of N,N'-methylenebisacrylamide, polyisomethacrylate, hydroperoxide, dialkyl peroxide, diacyl peroxide, peroxyester and ketone peroxide and their derivatives.

[0012] Optionally, the accelerator accounts for 0.5-1% of the sum of the mass of the first monomer and the second monomer, and the accelerator may include tetramethylethylenediamine.

[0013] Optionally, the pH of the mixed solution is adjusted using an alkaline solution having a concentration of 0.01 to 2 mol / L, and the alkaline solution may include one of aqueous ammonia, aqueous sodium hydroxide solution, aqueous potassium hydroxide solution, aqueous sodium carbonate solution, aqueous sodium bicarbonate solution and aqueous triethylamine solution.

[0014] Optionally, the ultrasonic treatment under ice bath and nitrogen protection lasts for 0.5 to 2 hours, the preset temperature is 30 to 65° C., and the polymerization time is 4 to 20 hours.

[0015] Optionally, the bubbles in the precursor solution are removed by ultrasonic removal under ice bath and nitrogen protection, and the ultrasonic duration is 0.5 to 2 hours;

[0016] Wherein, the preset temperature is 30-65°C, and the polymerization time is 4-20h.

[0017] Optionally, the hydrogel is cut into discs with a diameter of 12 to 18 mm, the amount of the salt solution containing zinc ions added is 10 to 40 μL, the concentration of the salt solution containing zinc ions is 1 to 3 mol / L, and the salt solution containing zinc ions may include one of zinc chloride, zinc sulfate, zinc trifluoromethanesulfonate, zinc acetate and zinc perchlorate.

[0018] A second aspect of the present invention provides a stretchable in-situ immersion double network hydrogel electrolyte.

[0019] The stretchable in-situ immersed double network hydrogel electrolyte can be prepared by the above method.

[0020] A third aspect of the present invention provides an aqueous zinc ion battery.

[0021] The aqueous zinc ion battery comprises the above-mentioned stretchable in-situ immersion double network hydrogel electrolyte.

[0022] A fourth aspect of the present invention provides the use of the above-mentioned stretchable in-situ immersion double network hydrogel electrolyte in the preparation of batteries.

[0023] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:

[0024] (1) The hydrogel electrolyte prepared by the present invention can improve the electrochemical performance of the hydrogel electrolyte in zinc ion battery applications by adjusting the pH of the precursor solution.

[0025] (2) The hydrogel electrolyte prepared by the present invention greatly reduces the consumption of zinc salt, improves the utilization rate of zinc salt and ensures its application as an electrolyte in zinc ion batteries.

[0026] (3) The hydrogel electrolyte prepared by the present invention can be used independently in zinc ion batteries, and can serve as an electrolyte and a separator at the same time, and can effectively inhibit the formation of dendrites.

[0027] (4) The hydrogel electrolyte prepared by the present invention has good mechanical properties and ionic conductivity. The hydrophilic functional groups on the polymer chain can adsorb or restrict active water, inhibit the precipitation of hydrogen and the formation of by-products, and optimize the Zn 2+ The diffusion of ions inhibits the formation of dendrites.

[0028] (5) The hydrogel electrolyte prepared by the present invention has excellent cycle stability when applied to zinc ion batteries, and exhibits a cycle stability voltage of 2000 h in a Zn||Zn symmetrical battery. When the full battery is composed, it can still maintain 79.5% of its capacity after 500 cycles at a current density of 1 A / g.

[0029] (6) The experimental steps for preparing the hydrosol electrolyte of the present invention are concise and easy to operate, which promotes the further development of gel polymer electrolytes for aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The above and other objects and / or features of the present invention will become more apparent through the following description in conjunction with the accompanying drawings, in which:

[0031] Figure 1 An optical photograph of a stretchable in-situ immersed double network hydrogel electrolyte assembled battery prepared in Example 5 of the present invention is shown;

[0032] Figure 2 The optical photograph of the stretchable in-situ immersed double network hydrogel electrolyte prepared in Example 5 of the present invention under deformation is shown;

[0033] Figure 3 The results show that the stretchable in-situ immersed double network hydrogel electrolyte composed of Zn||Zn symmetric battery prepared in Example 5 of the present invention and Comparative Example 1 has a current density of 1 mA / cm 2 The voltage-time curve below;

[0034] Figure 4 The long cycle performance diagram of the full battery composed of the double network self-healing hydrogel electrolyte prepared in Example 5 of the present invention and Comparative Example 1 is shown;

[0035] Figure 5 The ionic conductivity diagram of the iron symmetric battery composed of the double network self-healing hydrogel electrolyte prepared in Example 5 of the present invention and Comparative Example 1 is shown. DETAILED DESCRIPTION

[0036] Hereinafter, the stretchable in-situ immersion double network hydrogel electrolyte and its preparation method and application of the present invention will be described in detail in conjunction with exemplary embodiments.

[0037] Exemplary Embodiment 1

[0038] The present exemplary embodiment provides a method for preparing a stretchable in-situ immersion double network hydrogel electrolyte.

[0039] The preparation method may include the following steps:

[0040] S1. Prepare a uniform mixed solution of a first monomer, a second monomer, an initiator, a crosslinking agent and an accelerator.

[0041] In this embodiment, the first monomer is an amide monomer, the second monomer is an anhydride monomer, and the mass ratio of the first monomer to the second monomer is 1:(0.5-10), such as 1:0.5, 1:0.7, 1:1, 1:5, 1:6, 1:9.8, etc.

[0042] Among them, gel polymer electrolytes with different monomer mass ratios have different performances, and the differences in electrochemical properties of gel polymer electrolytes with different monomer mass ratios when applied to zinc-ion batteries are explored.

[0043] The amide monomer may include one of acrylamide, methacrylamide, N-isopropylacrylamide, N,N-diethylacrylamide, isobutoxymethylacrylamide, diacetone acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 2-(trifluoromethylsulfonamido)ethyl-methacrylate and N-allyl-2,2,2-trifluoroacetamide and derivatives thereof.

[0044] The anhydride monomer may include one of maleic anhydride, succinic anhydride, bromomaleic anhydride, dimethyl maleate, diethyl maleate, dibutyl maleate, diisooctyl maleate, maleic acid, fumaric acid, dibutyl fumarate and bis(2-ethylhexyl) fumarate and derivatives thereof.

[0045] In this embodiment, the initiator accounts for 0.2-2% of the sum of the mass of the first monomer and the second monomer, such as 0.2%, 0.5%, 0.6%, 1%, 1.2%, 1.9%, etc.

[0046] The initiator may include one of potassium persulfate, sodium persulfate, ammonium persulfate, and azobisisobutyronitrile.

[0047] Among them, different initiators have different initiation modes, and different mass percentages of initiators have different initiation rates of the gel electrolyte. The purpose of exploring the types and mass percentages of initiators is to optimize the most suitable initiation mode and initiation rate for the gel electrolyte of the system of the present invention to adapt to better electrochemical performance of zinc ion batteries.

[0048] In this embodiment, the cross-linking agent accounts for 0.01-1% of the sum of the mass of the first monomer and the second monomer, such as 0.01%, 0.02%, 0.06%, 0.1%, 0.2%, 0.5%, 0.95%, etc.

[0049] The crosslinking agent may include one or more of N,N'-methylenebisacrylamide, polymethacrylate, hydroperoxide, dialkyl peroxide, diacyl peroxide, peroxyester and ketone peroxide and derivatives thereof.

[0050] The present invention uses two monomers to copolymerize to prepare a hydrogel electrolyte. Different cross-linking agents have different cross-linking modes, and different cross-linking agent mass percentages will affect the cross-linking degree of the hydrogel. Based on this, it is hoped that by exploring the type and mass percentage of the cross-linking agent, a more suitable cross-linking mode and cross-linking degree can be optimized for application in aqueous zinc ion batteries.

[0051] In this embodiment, the accelerator accounts for 0.5-1% of the sum of the mass of the first monomer and the second monomer, such as 0.5%, 0.55%, 0.6%, 0.7%, 0.72%, 0.8%, 0.98%, etc.

[0052] The accelerator may include tetramethylethylenediamine.

[0053] Among them, selecting tetramethylethylenediamine as an accelerator can increase the polymerization rate while forming a hydrogel with higher mechanical strength and stability. Selecting the above mass percentage can reduce the side reactions between the monomer and the cross-linking agent, improve the purity and quality of the final product, and make its application in zinc ion batteries more advantageous.

[0054] S2. Adjust the pH of the mixed solution and stir it evenly to obtain a precursor solution.

[0055] In this embodiment, an alkaline solution is used to adjust the pH of the mixed solution, and the concentration of the alkaline solution is 0.01-2 mol / L, such as 0.01 mol / L, 0.02 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 1 mol / L, 1.2 mol / L, 1.9 mol / L, etc.

[0056] Among them, by adjusting the pH of the hydrogel precursor solution of the system of the present invention and optimizing the physical and chemical properties of the hydrogel, the electrochemical performance of the hydrogel applied to aqueous zinc ion batteries can be improved. After adjusting the pH, the pH value of the precursor solution is 1.5-5.5, such as 1.5, 1.8, 2.1, 3.5 and 5.4.

[0057] The alkaline solution may include one of aqueous ammonia, aqueous sodium hydroxide solution, aqueous potassium hydroxide solution, aqueous sodium carbonate solution, aqueous sodium bicarbonate solution, and aqueous triethylamine solution.

[0058] S3, removing bubbles from the precursor solution and forming a hydrogel by free radical polymerization at a preset temperature.

[0059] In this embodiment, the bubbles in the precursor solution are removed by ultrasound under ice bath and nitrogen protection, and the ultrasound duration is 0.5 to 2 h, such as 0.5 h, 0.55 h, 0.6 h, 0.8 h, 1 h, 1.2 h, 1.9 h, etc.

[0060] The hydrogel precursor solution can be completely deoxygenated within the above time range.

[0061] In this embodiment, the preset temperature is 30-65°C, such as 30°C, 32°C, 35°C, 40°C, 42°C, 50°C, 56°C, 60°C, 65°C, etc.

[0062] Different temperatures induce different speeds of hydrogel formation, resulting in different cross-linked network structures. Selecting the above temperature can better control the polymerization speed of the hydrogel in the system of the present invention.

[0063] In this embodiment, the polymerization time is 4 to 20 hours, such as 4 hours, 4.5 hours, 4.7 hours, 6 hours, 8.5 hours, 12 hours, 15.5 hours, 19.5 hours, etc.

[0064] Selecting the above time range can ensure that the precursor solution can be completely polymerized for use in aqueous zinc-ion batteries.

[0065] S4. Cut the hydrogel, drip a small amount of salt solution containing zinc ions on both sides of the cut hydrogel, sandwich it between two electrodes for in-situ immersion, and obtain a hydrogel electrolyte.

[0066] In this embodiment, the hydrogel is cut into discs with a diameter of 12 to 18 mm, and the amount of the salt solution containing zinc ions added is 10 to 40 μL, such as 10 μL, 11 μL, 15 μL, 20 μL, 25 μL, 30 μL, 39 μL, 40 μL, etc.

[0067] The concentration of the salt solution containing zinc ions is 1-3 mol / L, such as 1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.5 mol / L, 2 mol / L, 2.7 mol / L, 3 mol / L, etc.

[0068] The amount of the salt solution added is much smaller than the amount of electrolyte used in aqueous zinc-ion batteries, which can save costs while ensuring its application in aqueous zinc-ion batteries. The selected salt solution concentration belongs to low-concentration zinc salt, which is beneficial to the migration of zinc ions in zinc-ion batteries, thereby bringing better electrochemical performance.

[0069] The salt solution containing zinc ions may include one of zinc chloride, zinc sulfate, zinc trifluoromethanesulfonate, zinc acetate, and zinc perchlorate.

[0070] Exemplary Embodiment 2

[0071] The present exemplary embodiment provides a stretchable in-situ immersion double network hydrogel electrolyte.

[0072] The stretchable in-situ immersion double network hydrogel electrolyte can be prepared by the method described in Example 1.

[0073] Exemplary Embodiment 3

[0074] This exemplary embodiment provides an aqueous zinc ion battery.

[0075] The aqueous zinc ion battery includes the stretchable in-situ immersion double network hydrogel electrolyte described in Exemplary Embodiment 2.

[0076] Example 4

[0077] This exemplary embodiment provides an application of a stretchable in-situ immersion double network hydrogel electrolyte in preparing a battery.

[0078] In order to better understand the above exemplary embodiments, further description is given below in conjunction with specific embodiments.

[0079] Example 1

[0080] (1) Dissolve 2 g of isobutyloxymethyl acrylamide and 1 g of diethyl maleate in 20 mL of deionized water, stir at room temperature until transparent, add 0.03 g of potassium persulfate, 0.015 g of diacyl peroxide and 30 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L sodium bicarbonate aqueous solution into the mixed solution, adjust the pH to 6, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 80°C for 4 h; (4) Cut the hydrogel into discs with a diameter of 18 mm, drop 40 μL of a 1 mol / L zinc perchlorate aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte, and assemble it into a complete battery.

[0081] Example 2

[0082] (1) Dissolve 2.5 g of methacrylamide and 0.5 g of succinic anhydride in 20 mL of deionized water, stir at room temperature until transparent, add 0.03 g of sodium persulfate, 0.015 g of polyisopropylacrylate and 30 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L sodium hydroxide aqueous solution into the mixed solution, adjust the pH to 5, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and free radical polymerization at 80 ° C for 4 h to form a hydrogel; (4) Cut the hydrogel into discs with a diameter of 16 mm, drop 40 μL of a 1 mol / L zinc sulfate aqueous solution on both sides of the hydrogel and sandwich it between two pole pieces for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0083] Example 3

[0084] (1) Dissolve 2.5 g of N-isopropylacrylamide and 0.5 g of bromomaleic anhydride in 20 mL of deionized water, stir at room temperature until transparent, add 0.03 g of ammonium persulfate, 0.017 g of hydroperoxide and 30 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L potassium hydroxide aqueous solution into the mixed solution, adjust the pH to 4, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 70 ° C for 8 h; (4) Cut the hydrogel into discs with a diameter of 14 mm, drop 40 μL of a 1 mol / L zinc trifluoromethanesulfonate aqueous solution on both sides of the hydrogel and sandwich it between two pole pieces for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0085] Example 4

[0086] (1) Dissolve 2.5 g of N,N-diethylacrylamide and 0.5 g of dimethyl maleate in 20 mL of deionized water, stir at room temperature until transparent, add 0.03 g of azobisisobutylenenitrile, 0.017 g of dialkyl peroxide and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L sodium carbonate aqueous solution into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and free radical polymerization at 50 ° C for 12 h to form a hydrogel; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 40 μL of a 1 mol / L zinc acetate aqueous solution on both sides of the hydrogel and sandwich it between two pole pieces for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0087] Example 5

[0088] (1) Dissolve 2.5 g acrylamide and 0.5 g maleic anhydride in 20 mL deionized water, stir at room temperature until transparent, add 0.03 g potassium persulfate, 0.017 g N, N'-methylenebisacrylamide and 20 μL tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Add 0.1 mol / L ammonia water dropwise into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40 °C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drip 20 μL of 1 mol / L zinc chloride aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery, see Figure 1 Optical photograph of the assembled cell shown. Figure 2 The optical photograph of the stretchable in-situ immersed double network hydrogel electrolyte prepared according to Example 5 of the present invention under deformation is shown. Figure 2 The upper part is before deformation, and the lower part is after deformation.

[0089] Example 6

[0090] (1) Dissolve 2.5 g of diacetone acrylamide and 0.5 g of dibutyl maleate in 20 mL of deionized water, stir at room temperature until transparent, add 0.03 g of sodium persulfate, 0.017 g of peroxy ester and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a peroxy ester with a concentration of 0.1 mol / L into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and free radical polymerization at 40°C for 16 h to form a hydrogel; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 20 μL of a 1 mol / L zinc chloride aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0091] Example 7

[0092] (1) Dissolve 2.5 g of 2-acrylamido-2-methylpropanesulfonic acid and 0.5 g of diisooctyl maleate in 20 mL of deionized water, stir at room temperature until transparent, add 0.03 g of ammonium persulfate, 0.017 g of ketone peroxide and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop 0.1 mol / L ammonia water into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40°C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 10 μL of 1 mol / L zinc sulfate aqueous solution on both sides of the hydrogel and sandwich it between two pole pieces for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0093] Example 8

[0094] (1) Dissolve 2.5 g of 2-(trifluoromethylsulfonylamino)ethyl-methacrylate and 0.5 g of maleic acid in 20 mL of deionized water, stir at room temperature until transparent, add 0.03 g of azobisisobutyronitrile, 0.017 g of N,N'-methylenebisacrylamide and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L sodium hydroxide aqueous solution into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and free radical polymerization at 40°C for 12 h to form a hydrogel; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 10 μL of a 1 mol / L zinc trifluoromethanesulfonate aqueous solution on both sides of the hydrogel and sandwich it between two pole pieces for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0095] Example 9

[0096] (1) Dissolve 2.5 g of N-allyl-2,2,2-trifluoroacetamide and 0.5 g of fumaric acid in 20 mL of deionized water, stir at room temperature until transparent, add 0.03 g of potassium persulfate, 0.017 g of polyisopropylacrylate and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L potassium hydroxide aqueous solution into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40 ° C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 10 μL of a 1 mol / L zinc acetate aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0097] Example 10

[0098] (1) Dissolve 2.5 g acrylamide and 0.5 g dibutyl fumarate in 20 mL deionized water, stir at room temperature until transparent, add 0.03 g sodium persulfate, 0.017 g hydroperoxide and 20 μL tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L sodium carbonate aqueous solution into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40°C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 10 μL of a 1 mol / L zinc perchlorate aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0099] Embodiment 11

[0100] (1) Dissolve 2.5 g of methacrylamide and 0.5 g of bis(2-ethylhexyl) fumarate in 20 mL of deionized water, stir at room temperature until transparent, add 0.03 g of ammonium persulfate, 0.017 g of dialkyl peroxide and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L sodium bicarbonate aqueous solution into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40°C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 10 μL of a 1 mol / L zinc chloride aqueous solution on both sides of the hydrogel and sandwich it between two pole pieces for in-situ immersion, obtain a hydrogel electrolyte, and assemble it into a complete battery.

[0101] Comparative Example 1

[0102] (1) Dissolve 3 g of acrylamide in 20 mL of deionized water, stir at room temperature until it becomes transparent, add 0.03 g of potassium persulfate, 0.017 g of N,N'-methylenebisacrylamide and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop 0.1 mol / L ammonia water into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40°C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 20 μL of 1 mol / L zinc chloride aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0103] The stretchable in-situ immersion double network hydrogel electrolyte prepared in Example 5 and Comparative Example 1 was used to form a Zn||Zn symmetric battery. 2 The long-cycle charge-discharge test was carried out under Figure 3 The voltage-time curve is shown. Figure 3 It can be seen that the hydrogel electrolyte prepared in Example 5 can be stably cycled for 800 h and maintain a small hysteresis voltage, while the hysteresis voltage of Comparative Example 1 increases at around 150 h and fails at 340 h.

[0104] The double network self-healing hydrogel electrolyte prepared in Example 5 and Comparative Example 1 was used to form a full battery, and a full battery charge and discharge long cycle test was performed to obtain Figure 4 The long cycle performance diagram is shown. Figure 4 It can be seen that Example 5 with sodium vanadate positive electrode is 1A·g -1 The battery of Comparative Example 1 can stably cycle for 500 h at a current density of , and the capacity retention rate reaches 80%, while Comparative Example 1 becomes unstable after 280 h of cycling and eventually fails at 410 h.

[0105] The iron-iron symmetric battery composed of the double network self-healing hydrogel electrolyte prepared in Example 5 and Comparative Example 1 was subjected to impedance testing and obtained Figure 5 The ionic conductivity diagram is shown in Figure 2. Figure 5 It can be seen from the preferred embodiment 5 that the ionic conductivity reaches 16.77 mS·cm -1 , while the ionic conductivity of comparative example 1 is only 3.46 mS·cm -1 , indicating that the optimized gel electrolyte of the present invention is more conducive to improving the kinetics of aqueous zinc ion batteries.

[0106] Comparative Example 2

[0107] (1) Dissolve 3 g of acrylamide in 20 mL of deionized water, stir at room temperature until it becomes transparent, add 0.03 g of sodium persulfate, 0.017 g of polyisomethacrylate and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L sodium hydroxide aqueous solution into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40°C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 20 μL of a 1 mol / L zinc sulfate aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte, and assemble it into a complete battery.

[0108] Comparative Example 3

[0109] (1) 3 g of N-isopropylacrylamide was dissolved in 20 mL of deionized water, and the mixture was stirred at room temperature until transparent. 0.03 g of ammonium persulfate, 0.017 g of hydroperoxide and 20 μL of tetramethylethylenediamine were added, and the mixture was stirred at room temperature to obtain a mixed solution. (2) A 0.1 mol / L potassium hydroxide aqueous solution was dropped into the mixed solution, and the pH value was adjusted to 3. The mixture was stirred to obtain a precursor solution. (3) The bubbles in the precursor solution were removed by ultrasonic treatment for 30 min under the protection of nitrogen in an ice bath, and free radical polymerization was performed at 40°C for 12 h to form a hydrogel. (4) The hydrogel was cut into discs with a diameter of 12 mm, and 20 μL of a 1 mol / L zinc trifluoromethanesulfonate aqueous solution was dropped on both sides of the hydrogel and sandwiched between two electrodes for in-situ immersion to obtain a hydrogel electrolyte and assemble into a complete battery.

[0110] Comparative Example 4

[0111] (1) Dissolve 3 g of N,N-diethylacrylamide in 20 mL of deionized water, stir at room temperature until it becomes transparent, add 0.03 g of azobisisobutyronitrile, 0.017 g of dialkyl peroxide and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L sodium carbonate aqueous solution into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40 ° C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 20 μL of a 1 mol / L zinc acetate aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0112] Comparative Example 5

[0113] (1) Dissolve 3 g of isobutyloxymethyl acrylamide in 20 mL of deionized water, stir at room temperature until it becomes transparent, add 0.03 g of potassium persulfate, 0.017 g of diacyl peroxide and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L sodium bicarbonate aqueous solution into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40°C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 20 μL of a 1 mol / L zinc perchlorate aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte, and assemble it into a complete battery.

[0114] Comparative Example 6

[0115] (1) Dissolve 3 g of diacetone acrylamide in 20 mL of deionized water, stir at room temperature until it becomes transparent, add 0.03 g of sodium persulfate, 0.017 g of peroxy ester and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop a 0.1 mol / L triethylamine aqueous solution into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40 ° C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 20 μL of a 1 mol / L zinc chloride aqueous solution on both sides of the hydrogel and sandwich it between two pole pieces for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0116] Comparative Example 7

[0117] (1) Dissolve 3 g of 2-acrylamido-2-methylpropanesulfonic acid in 20 mL of deionized water, stir at room temperature until it becomes transparent, add 0.03 g of ammonium persulfate, 0.017 g of ketone peroxide and 20 μL of tetramethylethylenediamine, and stir at room temperature to obtain a mixed solution; (2) Drop 0.1 mol / L ammonia water into the mixed solution, adjust the pH to 3, and stir to obtain a precursor solution; (3) Remove bubbles in the precursor solution by ultrasonic treatment for 30 min under ice bath and nitrogen protection, and form a hydrogel by free radical polymerization at 40°C for 12 h; (4) Cut the hydrogel into discs with a diameter of 12 mm, drop 20 μL of 1 mol / L zinc sulfate aqueous solution on both sides of the hydrogel and sandwich it between two electrodes for in-situ immersion, obtain a hydrogel electrolyte and assemble it into a complete battery.

[0118] Comparative Example 8

[0119] (1) 3 g of 2-(trifluoromethylsulfonylamino)ethyl-methacrylate was dissolved in 20 mL of deionized water, and the mixture was stirred at room temperature until transparent. 0.03 g of ammonium persulfate, 0.017 g of hydroperoxide and 20 μL of tetramethylethylenediamine were added, and the mixture was stirred at room temperature to obtain a mixed solution. (2) A 0.1 mol / L potassium hydroxide aqueous solution was dropped into the mixed solution, and the pH value was adjusted to 3. The mixture was stirred to obtain a precursor solution. (3) The bubbles in the precursor solution were removed by ultrasonic treatment for 30 min under the protection of nitrogen in an ice bath, and a hydrogel was formed by free radical polymerization at 40°C for 12 h. (4) The hydrogel was cut into discs with a diameter of 12 mm, and 20 μL of a 1 mol / L zinc trifluoromethanesulfonate aqueous solution was dropped on both sides of the hydrogel and sandwiched between two electrodes for in-situ immersion to obtain a hydrogel electrolyte and assemble into a complete battery.

[0120] Comparative Example 9

[0121] (1) 3 g of N-allyl-2,2,2-trifluoroacetamide was dissolved in 20 mL of deionized water, and the mixture was stirred at room temperature until transparent. 0.03 g of azobisisobutyronitrile, 0.017 g of dialkyl peroxide and 20 μL of tetramethylethylenediamine were added, and the mixture was stirred at room temperature to obtain a mixed solution. (2) A 0.1 mol / L sodium carbonate aqueous solution was dropped into the mixed solution, and the pH value was adjusted to 3. The mixture was stirred to obtain a precursor solution. (3) The bubbles in the precursor solution were removed by ultrasonic treatment for 30 min under the protection of nitrogen in an ice bath, and a hydrogel was formed by free radical polymerization at 40 ° C for 12 h. (4) The hydrogel was cut into discs with a diameter of 12 mm, and 20 μL of a 1 mol / L zinc acetate aqueous solution was dropped on both sides of the hydrogel and sandwiched between two electrodes for in-situ immersion to obtain a hydrogel electrolyte and assemble into a complete battery.

[0122] The comparative examples of the present invention are hydrogel electrolytes polymerized by different types of amide monomers. As shown in Table 1, by comparing the comparative examples of the same type of amide monomers with the amide-anhydride examples, it can be found that the introduction of anhydride monomers is beneficial to improving the physical and chemical properties of the gel electrolyte, and can also improve its application in aqueous zinc ion batteries.

[0123] Table 1 Test data of comparative example

[0124]

[0125]

[0126] Although the present invention has been described above in conjunction with the exemplary embodiments and the accompanying drawings, it should be apparent to those skilled in the art that various modifications may be made to the above-described embodiments without departing from the spirit and scope of the claims.

Claims

1. A method for preparing a stretchable in-situ immersion double network hydrogel electrolyte, characterized in that: The method comprises: 1) preparing a uniform mixed solution of a first monomer, a second monomer, an initiator, a crosslinking agent and an accelerator; 2) adjusting the pH of the mixed solution and stirring it evenly to obtain a precursor solution; 3) removing bubbles from the precursor solution and forming a hydrogel by free radical polymerization at a preset temperature; 4) Cut the hydrogel, drip a small amount of salt solution containing zinc ions on both sides of the cut hydrogel, sandwich it between two electrodes for in-situ immersion, and obtain a hydrogel electrolyte.

2. The method for preparing a stretchable in-situ immersion double network hydrogel electrolyte according to claim 1, characterized in that: In step 1), the first monomer is an amide monomer, the second monomer is an anhydride monomer, and the mass ratio of the first monomer to the second monomer is 1:(0.5-10); The amide monomers include acrylamide, methacrylamide, N-isopropylacrylamide, N,N-diethylacrylamide, isobutoxymethylacrylamide, diacetone acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 2-(trifluoromethylsulfonamido)ethyl-methacrylate and N-allyl-2,2,2-trifluoroacetamide and derivatives thereof; The acid anhydride monomer includes one of maleic anhydride, succinic anhydride, bromomaleic anhydride, dimethyl maleate, diethyl maleate, dibutyl maleate, diisooctyl maleate, maleic acid, fumaric acid, dibutyl fumarate and bis(2-ethylhexyl) fumarate and derivatives thereof.

3. The method for preparing a stretchable in-situ immersion double network hydrogel electrolyte according to claim 1, characterized in that: In step 1), the initiator accounts for 0.2-2% of the sum of the mass of the first monomer and the second monomer, and the initiator includes one of potassium persulfate, sodium persulfate, ammonium persulfate and azobisisobutyronitrile.

4. The method for preparing a stretchable in-situ immersion double network hydrogel electrolyte according to claim 1, characterized in that: In step 1), the cross-linking agent accounts for 0.01-1% of the sum of the mass of the first monomer and the second monomer, and the cross-linking agent includes one or more of N,N'-methylenebisacrylamide, polymethacrylate, hydroperoxide, dialkyl peroxide, diacyl peroxide, peroxyester and ketone peroxide and their derivatives; In step 1), the accelerator accounts for 0.5-1% of the sum of the mass of the first monomer and the second monomer, and the accelerator includes tetramethylethylenediamine.

5. The method for preparing a stretchable in-situ immersion double network hydrogel electrolyte according to claim 1, characterized in that: In step 2), an alkaline solution is used to adjust the pH of the mixed solution, the concentration of the alkaline solution is 0.01-2 mol / L, and the alkaline solution includes one of ammonia water, sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, sodium carbonate aqueous solution, sodium bicarbonate aqueous solution and triethylamine aqueous solution.

6. The method for preparing a stretchable in-situ immersion double network hydrogel electrolyte according to claim 1, characterized in that: In step 3), the bubbles in the precursor solution are removed by ultrasound under ice bath and nitrogen protection, and the ultrasound duration is 0.5 to 2 hours; The preset temperature is 30-65° C., and the polymerization time is 4-20 hours.

7. The method for preparing a stretchable in-situ immersion double network hydrogel electrolyte according to claim 1, characterized in that: The hydrogel electrolyte in step 4) is cut into discs with a diameter of 12 to 18 mm, the amount of the salt solution containing zinc ions added is 10 to 40 μL, the concentration of the salt solution containing zinc ions is 1 to 3 mol / L, and the salt solution containing zinc ions includes one of zinc chloride, zinc sulfate, zinc trifluoromethanesulfonate, zinc acetate and zinc perchlorate.

8. A stretchable in-situ immersion double network hydrogel electrolyte, characterized in that: The stretchable in-situ immersion double network hydrogel electrolyte is prepared by the method according to any one of claims 1 to 7.

9. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery comprises the stretchable in-situ immersion double network hydrogel electrolyte described in claim 8.

10. Use of the stretchable in-situ immersion double network hydrogel electrolyte according to claim 8 in preparing a battery.

Citation Information

Patent Citations

  • Double network polymer hydrogel and preparation method thereof

    CN102226007A

  • Novel hydrogel with ultrahigh mechanical strength and chemical stability

    CN105199281A

  • Zinc ion battery based on ionic liquid-aqueous gel double-layer electrolyte and preparation method thereof

    CN117594885A

  • High-water-retention dual-network hydrogel electrolyte as well as preparation method and application thereof

    CN118126354A

  • Hydrogel electrolyte and preparation method and application thereof

    CN118388705A

Cited By

  • Preparation method of double-network hydrogel electrolyte containing composite zinc salt

    CN122136187A